Horseshoe Abscess in Conjunction with Insidious Spidermoid Anal Cancer - Adolfo, García Sánchez Morelos; Mireya, De La Fuente González; Isabel, Estrada Rodríguez María; Fernando, Juárez Moyrón Miguel; Yamileth, Jiménez Bonola; Pazos, Mauricio Israel Flores (British Journal of Healthcare and Medical Research, 2022)
Anal squamous cell cancer is extremely rare in terms of it´s presentation, an incidence of 1-2% of all neoplasms of the digestive tract is estimated. The objective is the presentation of a case and review of the literature. Case: 44-years-old male who started 14 days earlier, with increased perianal and intergluteal volumen, with an amorphous, irregular, poorly limited, hyperthermic, hard, stony extension, vegetating large elements; surgery is performed with abscess drainage and biopsy, diagnosing squamous cell carcinoma. Discussion: the treatment is chemoradiotherapy, surgery is reserved for failure of this; in the initial stage, survival is greater than 73% at 5 years and in recurrent cases, surgical rescue is relegated with results of 48% in survival. It is concluded that it is irrefutable that any lesion of the colon, rectum and anus, tumor, irregular or abnormal tissue, be biopsied and analyzed histopathologically. In addition, there is the delay in diagnosis, which is associated with the cultural beliefs of patients or their idiosyncrasy, with a shortage of qualified personnel and infrastructure in the public health sector, which is very common in developing countries.